2017
DOI: 10.1177/0739456x17702443
|View full text |Cite
|
Sign up to set email alerts
|

Are Walkable Neighborhoods More Resilient to the Foreclosure Spillover Effects?

Abstract: Since 2007, many studies have explored the price spillover effect of foreclosures. However, none has examined the potential moderating effects of built-environment characteristics such as walkability. By using the interaction term between neighborhood foreclosure and walkability, this study found that property values in walkable neighborhoods were less subject to foreclosure spillover, but this was only significant for middle/high-income neighborhoods. Walkable neighborhoods were shown to offer more advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The study and the observation of the raster maps has brought to light critical morphological aspects that can be corrected in order to design a more resilient environment, which can contemplate solutions attentive to individual specificities by enhancing the use of the roads as a public space [75]. Moreover, the value of the maps does not only concern morphological aspects, but also allows to highlight sociological elements.…”
Section: Discussionmentioning
confidence: 99%
“…The study and the observation of the raster maps has brought to light critical morphological aspects that can be corrected in order to design a more resilient environment, which can contemplate solutions attentive to individual specificities by enhancing the use of the roads as a public space [75]. Moreover, the value of the maps does not only concern morphological aspects, but also allows to highlight sociological elements.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that individuals are willing to pay a premium price to purchase housing in walkable neighborhoods (Gilderbloom et al, 2015;Hu et al, 2014b;Rauterkus & Miller, 2011;Yencha, 2019). Furthermore, walkable neighborhoods are considered more resilient during economic downturns, which allows them to retain more value compared to non-walkable neighborhoods (Won et al, 2018;Xu et al, 2018).…”
Section: Green Theory: Pollution and Walkabilitymentioning
confidence: 99%
“…Previous research also found that land price leads to more volatile trends in the real estate market compared with housing price [17,18], and different factors determine land and improvement components [19]. The extensive hedonic price literature has shown housing prices are a function of various factors ranging from structural (e.g., built year, lot size, and number of rooms) and financial characteristics (e.g., foreclosed status) to neighborhood (e.g., socioeconomic, safety, built environments) characteristics [20,21]. Land price has long relied on monocentric models mainly explained by accessibility (e.g., distance to the central business district) and land use density as essential concepts in land economic theories [22,23].…”
Section: Introductionmentioning
confidence: 99%